2005
DOI: 10.1038/sj.bjc.6602913
|View full text |Cite
|
Sign up to set email alerts
|

‘A phase II study of oral uracil/ftorafur (UFT®) plus leucovorin combined with oxaliplatin (TEGAFOX) as first-line treatment in patients with metastatic colorectal cancer’

Abstract: This phase II trial was performed to evaluate the efficacy and tolerability of a new combination of Uracil/Ftorafur (UFT s )/leucovorin (LV) and oxaliplatin in patients (pts) with metastatic colorectal cancer (MCRC) who had not received prior chemotherapy for metastatic disease. Between February 2002 and October 2002, 64 patients received UFT s 300 mg m À2 day À1 and LV 90 mg day À1 from day 1 to day 14 combined with oxaliplatin 130 mg m À2 on day 1, every 3 weeks. All patients were evaluable for safety analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…The toxicity profile observed with TEGAFOX and TEGAFIRI in the present study compares favourably with that reported in other phase II trials (Feliu et al, 2004, (Mendez et al, 2005Bennouna et al, 2006). In particular, the rate of TEGAFOX grade 3 -4 neurotoxicity was around 14 -15% in Bennouna and Feliu studies as compared with 6% in our study.…”
Section: Discussionsupporting
confidence: 78%
“…The toxicity profile observed with TEGAFOX and TEGAFIRI in the present study compares favourably with that reported in other phase II trials (Feliu et al, 2004, (Mendez et al, 2005Bennouna et al, 2006). In particular, the rate of TEGAFOX grade 3 -4 neurotoxicity was around 14 -15% in Bennouna and Feliu studies as compared with 6% in our study.…”
Section: Discussionsupporting
confidence: 78%
“…The results from the present study confirm that alternating irinotecan and oxaliplatin during treatment with UFT with LV allows patients to receive an effective triple-drug regimen without the excessive haematological toxicities often observed with such treatments. The combination of UFT with LV plus irinotecan and oxaliplatin was highly effective, with excellent ORRs that were consistent with the phase I study results and better than those reported for UFT with LV plus irinotecan (Mendez et al, 2005;Delord et al, 2007;Bajetta et al, 2007a) or UFT with LV plus oxaliplatin (Feliu et al, 2004;Rosati et al, 2005;Bennouna et al, 2006;Bajetta et al, 2007a), providing further support for the up-front treatment approach. Particularly notable was the fact that all patients treated at the MTD benefited from therapy, with partial responses in 68% patients and stable disease in 32%.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, patients in the UFT with LV group had a significantly lower incidence of stomatitis and other gastrointestinal events than 5-FU/LV. A number of small studies have shown that UFT can be combined with oxaliplatin (Feliu et al, 2004;Rosati et al, 2005;Bennouna et al, 2006;Bajetta et al, 2007a) or irinotecan (Mendez et al, 2005;Delord et al, 2007;Bajetta et al, 2007a), both combinations being effective and well tolerated in first-line mCRC.…”
mentioning
confidence: 99%
“…In these patients, major grade III/IV toxicities were diarrhea (16.9%) and peripheral neuropathy (12.7%). In 2006, Bennouna et al reported results of the regimen of OXA 130 mg/m 2 given on day 1 combining the administration of oral tegafur-uracil 300 mg/m 2 /day and LV 90 mg/day from day 1 to 14 in a 21-day cycle (TEGAFOX) used as Wrst-line treatment for patients with metastatic colorectal cancer [28]. Major grade III/IV toxicities caused by the abovementioned regimen were sensory neuropathy (15%), asthenia (13%) and diarrhea (11%).…”
Section: Discussionmentioning
confidence: 99%